2009
DOI: 10.1177/1043454209340326
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment of Children With Cancer

Abstract: Regardless of which parts of the world they live in, most children will develop and grow at a similar rate if proper nutrition is ensured. Children from developing countries are at risk for primary malnutrition. Children undergoing anticancer therapy are at higher risk for secondary malnutrition, including obesity and growth retardation. Periodic nutritional assessments are important for planning effective dietary interventions for such children. In this review, we describe malnutrition as it occurs in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 73 publications
1
50
2
1
Order By: Relevance
“…Table 1 reveals A total of 30 children with newly diagnosed ALL were included in this study, their age range from (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years, mean age (5.4 ± 3.4SD). Sixteen were males and fourteen were females, reveals that 16 (53.3%) of patients included in this study were males and 14 (46.6%) were females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 reveals A total of 30 children with newly diagnosed ALL were included in this study, their age range from (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years, mean age (5.4 ± 3.4SD). Sixteen were males and fourteen were females, reveals that 16 (53.3%) of patients included in this study were males and 14 (46.6%) were females.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition can lead to a decreased immune function, in already immune compromised patients; delay wound healing and reduce drug metabolism. Also, as mentioned earlier it can be a contributing factor to death and poor prognosis [1,8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This omission, of which the Dutch authors are aware (their reference 21), is compounded by a mis-representation of the data; the authors of the Central American study did not "promote the use of BMI as an indicator of nutritional status" in children with cancer, preferring arm anthropometry for reasons articulated previously [3]. Loeffen and colleagues may also take note of a study conducted subsequently in Guatemala that reported on the restoration of good survival prospects for children with acute lymphoblastic leukemia who were malnourished at diagnosis but normalized their nutritional status during therapy [4].…”
mentioning
confidence: 99%
“…This assessment includes medical history, physical examination, biochemical and hematological data, such as visceral proteins, blood glucose levels, and lipid profiles, hemoglobin, hematocrit and lymphocyte counts, anthropometric measurements, and food and nutrition history. Visceral proteins such as prealbumin, transferrin and retinol-binding protein have emerged as indicators of nutritional status [4,5]. Anthropometric measurements are a primary component of the nutrition assessment process in pediatric oncology patients.…”
Section: Introductionmentioning
confidence: 99%